Transcription activity of rRNA genes correlates with a tendency towards intergenomic homogenization in Nicotiana allotetraploids - Dadejová, Martina; Lim, K Yoong; Soucková-Skalická, Kamila; Matyášek, Roman; Grandbastien, Marie-Angéle; Leitch, Andrew; Kovařík, Aleš (The New phytologist, 2007)
This paper establishes relationships between two aspects of ribosomal DNA (rDNA) biology: epigenetic silencing of rDNA loci; and homogenization leading to concerted evolution. Here, we examined rDNA inheritance and expression patterns in three natural Nicotiana allopolyploids (closest living descendants of diploid parents are given), N. rustica (N. paniculata x N. undulata), N. tabacum (N. sylvestris x N. tomentosiformis) and N. arentsii (N. undulata x N. wigandioides), and synthetic F(1) hybrids and allopolyploids. The extent of interlocus rDNA homogenization decreased in the direction N. arentsii > N. tabacum > N. rustica. The persistence of parental rDNA units in one of the subgenomes was associated with their transcription inactivity and likely heterochromatization. Of synthetic hybrids and polyploids only N. paniculata x N. undulata showed strong uniparental transcriptional silencing of rDNA triggered already in F(1). Epigenetic patterns of expression established early in allopolyploid nucleus formation may render units susceptible or resistant to homogenization over longer time-frames. We propose that nucleolus-associated transcription leaves rDNA units vulnerable to homogenization, while epigenetically inactivated units, well-separated from the nucleolus, remain unconverted.
Keywords: genetická transkripce; Genome, Plant; Nicotiana; Transcription, Genetic; ribozomální DNA; Genes, rRNA; Gene Silencing; RNA rostlin; geny rRNA; RNA, Plant; umlčování genů; polyploidie; DNA, Ribosomal; Polyploidy; genom rostlinný; tabák